Spreading the Good News: Analyzing Socially Shared Inspirational News Content. (September 2019) - Ji, Qihao; Raney, Arthur A.; Janicke-Bowles, Sophie H.; Dale, Katherine R.; Oliver, Mary Beth; Reed, Abigail; Seibert, Jonmichael; Raney, Arthur A.
Past research indicates that people often share awe-inspiring news online. However, little is known about the content of those stories. In this study, more broadly defined "inspirational" articles shared through The New York Times website over a 6-month period were analyzed, with the goals of describing the content and identifying characteristics that might predict inspirationality and measures of retransmission. The results provided a snapshot of content found within inspirational news stories; they also revealed that self-transcendent language use predicted the inspirationality of a news story, as well as how long an article appeared on a most shared list.